2022
DOI: 10.1186/s13287-022-02828-w
|View full text |Cite
|
Sign up to set email alerts
|

Human primitive mesenchymal stem cell-derived retinal progenitor cells improved neuroprotection, neurogenesis, and vision in rd12 mouse model of retinitis pigmentosa

Abstract: Background Currently, there is no treatment for retinal degenerative diseases (RDD) such as retinitis pigmentosa (RP). Stem cell-based therapies could provide promising opportunities to repair the damaged retina and restore vision. Thus far, primarily adult mesenchymal stem cells (MSCs) have been investigated in preclinical and clinical studies, and the results have not been convincing. We applied a new approach in which primitive (p) MSC-derived retinal progenitor cells (RPCs) were examined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Brown and colleagues used primitive MSC-derived retinal progenitor cells in rd12 mouse models. They tracked PKH26 dyed cells and found that cells were able to integrate and counter inflammation [ 154 ]. Overall, the advantages of BMSCs include their ability to migrate towards lesion sites, the ability for trans-differentiation, and the simplicity in extracting and manipulating CD34+ cells.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Brown and colleagues used primitive MSC-derived retinal progenitor cells in rd12 mouse models. They tracked PKH26 dyed cells and found that cells were able to integrate and counter inflammation [ 154 ]. Overall, the advantages of BMSCs include their ability to migrate towards lesion sites, the ability for trans-differentiation, and the simplicity in extracting and manipulating CD34+ cells.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…RPCs can be derived from ESCs, iPSCs and MSCs, among others. These cells show promising results with increased BCVA outcomes in injected eyes but are relatively self-limiting regarding expansion compared to pluripotent cell lines [ 319 , 320 ]. RPCs also retain their capacity to differentiate in preclinical studies, which poses challenges post-transplantation [ 311 , 319 , 321 ].…”
Section: Gene-independent Strategiesmentioning
confidence: 99%
“…These cells show promising results with increased BCVA outcomes in injected eyes but are relatively self-limiting regarding expansion compared to pluripotent cell lines [ 319 , 320 ]. RPCs also retain their capacity to differentiate in preclinical studies, which poses challenges post-transplantation [ 311 , 319 , 321 ]. MSCs, with their lower cell potency, are considered safer and have more long-term data on the risk of tumorigenesis.…”
Section: Gene-independent Strategiesmentioning
confidence: 99%
“…Activation of JAK/STAT signaling has a protective effect on the RP retina. pMSC-derived retinal progenitor cell transplantation increased PR preservation in rd12 mice, and this protection was partially mediated by activation of the JAK/STAT pathway ( 100 ).…”
Section: Mechanisms Related To Inflammation In Rpmentioning
confidence: 99%